Pelatihan Perencanaan Event, Perhitungan Waktu Dan Lokasi Event Bagi Peserta Didik Zillenial Action - Nisa Lathifah; Shinta Hartini Putri; Zulfanida Nurul Sadiyyah; Hanafi Hanafi; Fanzah Evan Ervansyah (Jurnal Bhakti Karya dan Inovatif, 2025)
The event planning, time calculation, and event location selection training program for Zillenial Action students is designed in a practical and interactive manner to adapt to the characteristics of Generation Z and millennials who love visual, collaborative, and technology-based learning. The training began with brainstorming to explore participants' understanding of the event, followed by the presentation of practical material by resource persons who are experienced in the field of academics and event management. The material presented included planning the theme and concept of the event, determining targets, choosing time and location, and strategies for overcoming obstacles in organizing the event. With interactive discussion methods, it encourages creative thinking and enriches training materials. Participants also conducted a simple event planning simulation, followed by presentations and discussions to deepen understanding. The program aims to equip participants with modern event planning skills that are relevant to the needs of today's audience. Through the right time calculation and strategic location selection, it is hoped that participants will be able to organize an effective, efficient, and memorable event in various professional and community contexts. The results of the training showed that participants were able to understand the concept of event planning, manage budgets and resources efficiently, manage time effectively, and choose strategic locations according to the event audience.